Soft methods, hard targets: regional alcohol managers as a policy network. (August 2014) - Lloyd, Charlie; Thom, Betsy; MacGregor, Susanne; Herring, Rachel; Godfrey, Christine; Toner, Paul; Tchilingirian, Jordan
Abstract Regional Alcohol Managers (RAMs) were employed in the nine English health regions over 2008–2011. Their mission was to impact on the 'hard target' of Alcohol-Related Hospital Admissions (AHRAs) through the 'soft methods' of persuasion and influence: working with local partners on evidence-based interventions. Drawing on a qualitative evaluation, this article shows how a central government policy imperative (ARHAs) led to 'government at a distance' responses, including the introduction of RAMs. The processes involved in shaping and delivering this function bore the hallmarks of a complex, interactive policy network model, involving individuals whose bearings and roles were flexible and sometimes ambiguous. While there were overlaps and blurring of boundaries, there were three levels of policy network: central government, regional and local. As the 'network in the middle', the RAMs were pulled in both directions by conflicting agendas but were also able to have an impact on central and local policy.